2016
DOI: 10.1038/mp.2016.112
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of the p66Shc adaptor protein reverses cognitive deficits and improves mitochondrial function in an APP transgenic mouse model of Alzheimer’s disease

Abstract: The mammalian ShcA adaptor protein p66 is a key regulator of mitochondrial reactive oxygen species (ROS) production and has previously been shown to mediate amyloid β (Aβ)-peptide-induced cytotoxicity in vitro. Moreover, p66 is involved in mammalian longevity and lifespan determination as revealed in the p66 knockout mice, which are characterized by a 30% prolonged lifespan, lower ROS levels and protection from age-related impairment of physical and cognitive performance. In this study, we hypothesized a role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 82 publications
3
21
0
Order By: Relevance
“…Moreover, genetic ablation of p66Shc in an AD mouse model (APP/PS1) leads to a reversal of age-dependent cognitive decline, independent of Aβ levels and plaque formation. The improvement in cognitive function in APP/PS1 mice lacking p66Shc was associated with a reversal of mitochondrial complex I dysfunction, increased ATP production, and reduced ROS levels in cortical tissue 115 . A recent study also revealed that p66Shc knockout (−/−) mice were protected from diabetes-induced cognitive decline, which correlated with a decrease in oxidative stress and pro-inflammatory markers in the brain 116 .…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, genetic ablation of p66Shc in an AD mouse model (APP/PS1) leads to a reversal of age-dependent cognitive decline, independent of Aβ levels and plaque formation. The improvement in cognitive function in APP/PS1 mice lacking p66Shc was associated with a reversal of mitochondrial complex I dysfunction, increased ATP production, and reduced ROS levels in cortical tissue 115 . A recent study also revealed that p66Shc knockout (−/−) mice were protected from diabetes-induced cognitive decline, which correlated with a decrease in oxidative stress and pro-inflammatory markers in the brain 116 .…”
Section: Discussionmentioning
confidence: 88%
“…p66Shc is encoded by the ShcA gene locus that is expressed as three isoforms of about 46, 52, and 66 kDa in mammals. Some studies have shown that p66Shc plays a pivotal role in regulating the intracellular redox balance in vitro 12 and ablation of p66Shc results in less OS-induced tissue damage in vivo 13 15 .…”
Section: Introductionmentioning
confidence: 99%
“…P66 isoform of SHC1 (p66shc) proapoptotic ROS-elevating SHC family adaptor is an important regulator of redox homeostasis [31]. Genetic ablation of the p66Shc has been shown to reverse cognitive deficits and improve mitochondrial function in an APP transgenic mouse model of Alzheimer's disease [32]. In the present study, we found that OGD significantly increased total protein expression and acetylated form of P66shc, which was involved in the ROS generation and activation of mitochondrial apoptosis and cytotoxicity.…”
Section: Discussionmentioning
confidence: 49%